Demographic and genetic factors influence the abundance of infiltrating immune cells in human tissues - Andrew R. Marderstein (Nature Portfolio, 2020)
Immune infiltration provides critical information for health and disease, yet it is unclear what factors influence infiltration levels. Here, the authors analyze human tissue transcriptomes from the Genotype-Tissue Expression project to find infiltration patterns regulated by age, sex and host genetic information.